The Neo-commedia dell'arte or "The invention of a tradition": Carlo Boso and Leo de Berardinis, two modern capocomici (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This article presents the Commedia dell’arte in the 20th century as an “Invented Tradition”, following the perspective of the studies by Hobsbawm (1983), and can be named Neo-Commedia dell’arte. For this, two brief case studies are presented, from the plays Il Falso Magnifico [The False Magnificent] (Carlo Boso) (and Il Return di Scaramouche [The Return of Scaramouche] (Leo de Berardinis).
Keywords: Commedia dell'arte; Staging; Acting; Carlo Boso; Leo de Berardinis